Hypoglicemia Risk Factors on Hospitalized Type 2 Diabetes Mellitus Patients - Jayanti, Meilani; Lestari, Keri; Abdulah, Rizky (Pharmacology and Clinical Pharmacy Research, 2018)
Hypoglycemia is one of the most important complications of diabetes treatment and it becomes an obstacle in hypoglycemia medication. Besides, hypoglycemia can cause nerve damage and impaired cognitive function so that it influences the patients mortality, morbidity, and quality of life. Recognition of hypoglycemia risk factors, blood glucose monitoring, selection of appropriate regimens and educational programs for healthcare professionals and patients with diabetes are the major issues to maintain good glycemic control, minimize the risk of hypoglycemia, and prevent long-term complications. This research employs retrospective method and the design of the research is case control. The sample of this research is 72 patients with type 2 diabetes which is divided into two groups. The first group is case and It consists of 23 patients (31,9%) getting hypoglycemia. Then, the second group is control and it consists of 49 patients (68,1%). In the second group the 49 patients do not get hypoglycemia and they do not receive any hypoglycemia medication in the hospital. The Results of multivariate logistic regression analysis shows that there is a significant different between the variables reduction in food intake (p 0,011) and lower laboratory result of HbA1C (p 0,003) on the incidence of hypoglycemic, where the variable reduction in food intake has the strong relationship with most major hypoglycemic (OR 9,329). On the other hand, other variables such as the use of antidiabetic drugs, diabetes duration, age, comorbidities and polypharmacy showed no significant association with hypoglycemic events. Thus, the hypoglycemic risk factors in patients with type 2 diabetes receiving antidiabetic therapy due to reduction in food intake and lower laboratory results of HbA1C. Patients with reduction in food intake at risk of hypoglycemic events nine times greater than patients with normal food intake. Keywords: type 2 diabetes mellitus, hypoglycemia, food intake, HbA1C